Contribuição para a padronização de extratos de folhas de Cecropia glaziovii Snethl: estudos de variação sazonal e intra-específica de flavonóides eproantocianidinas, de metodologias de extração e de atividade vasorelaxante - Pilar Ester Luengas Caicedo (2005)
Cecropia glaziovii Snethl. is a traditional medicinal plant whose antihypertensive effect was shown to be related to flavonoids and proanthocyanidins. The present work describes studies on the sazonal and intraspecific variation of these metabolite classes, whose contents were determined by spectrophotometry, for samples of young and mature leaves collected from native, cultivated and clone trees, along the dried and rainy periods of a year. The flavonoid and proanthocyanidin contents varied from 0.64 +/- 0.21% to 3.44 +/-0.56% and from 2.23 +/- 0.89% to 5.36 +/- 0.68% , respectively, for the assayed populations. As expected, a greater variability was observed for native than for cultivated and clone trees. HPLC analyses allowed the identification of protocatechic acid,chlorogenic acid, (+)-catechin, (-)-epicatechin, orientin, isoorientin, isovitexin and isoquercetrin, as well as the quantification of chlorogenic acid, orientin and isoorientin in young and mature leaves of C. glaziovii. The percentage of chlorogenic acid varied from 0.03% to 2.39%, for orientin the contents were from 0.01 to 0.42% and for isoorientin, from 0.08 to 1.16%. Aiming to develop a standardized extract of C. glaziovii leaves, several solvents and extraction methodologies were assayed in a bench scale evaluating the effect of the solvent, the ratio drug/solvent and the extraction technique in the flavonoid and proanthocyanidin contents, as well in the vasorelaxant activity on rat aorta rings pre-contracted with phenylephrine. Crude extracts of C. glaziovii leaves were partitionated by extraction with immiscible solvents followed by column chromatography on Sephadex LH-20 and the obtained fractions were characterized by their HPLC profiles, flavonoid and proanthocyanidin contents, aswell vasorelaxant acivity. The results confirm the effect of flavonoid andproanthocyanidin in the vasorelaxant activity but it seems they are not totally responsible for the experimentally previously observed anti-hypertensive effect of C. glaziovii leaves. The similarities on the phytochemical and pharmacological profiles of C glaziovii and Crataegus suggest its possible use as a Crataegus substitute.